2011
DOI: 10.1371/journal.pone.0019000
|View full text |Cite
|
Sign up to set email alerts
|

Stage-Specific Pathways of Leishmania infantum chagasi Entry and Phagosome Maturation in Macrophages

Abstract: The life stages of Leishmania spp. include the infectious promastigote and the replicative intracellular amastigote. Each stage is phagocytosed by macrophages during the parasite life cycle. We previously showed that caveolae, a subset of cholesterol-rich membrane lipid rafts, facilitate uptake and intracellular survival of virulent promastigotes by macrophages, at least in part, by delaying parasitophorous vacuole (PV)-lysosome fusion. We hypothesized that amastigotes and promastigotes would differ in their r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 54 publications
4
54
0
2
Order By: Relevance
“…One study investigated the role of the sodium ion channel NaV1.5 on phagosome maturation in human peripheral blood monocytes, which were differentiated to macrophages and treated with dead bacillus Camille-Guerin, a model for mycobacterial infection. 452a Confocal immunofluorescence microscopy showed that NaV1.5 was localized in the endosomes near the periphagosome region. Knockdown of NaV1.5 caused about a 9-fold decrease in phagocytosis of the dead bacillus.…”
Section: Organelle Dynamics Interactions and Maturationmentioning
confidence: 99%
See 3 more Smart Citations
“…One study investigated the role of the sodium ion channel NaV1.5 on phagosome maturation in human peripheral blood monocytes, which were differentiated to macrophages and treated with dead bacillus Camille-Guerin, a model for mycobacterial infection. 452a Confocal immunofluorescence microscopy showed that NaV1.5 was localized in the endosomes near the periphagosome region. Knockdown of NaV1.5 caused about a 9-fold decrease in phagocytosis of the dead bacillus.…”
Section: Organelle Dynamics Interactions and Maturationmentioning
confidence: 99%
“…451 Next, phagosome-lysosome interactions with pathogen-based models 452 and phagosome-autophagosome interactions are discussed. 453 Finally we discuss recent insights into phagosome interactions with other membrane systems such as the plasma membrane 454 , ER, 455 and Golgi.…”
Section: Organelle Dynamics Interactions and Maturationmentioning
confidence: 99%
See 2 more Smart Citations
“…Mycobacterium tuberculosis uses lipid rafts to enter alveolar epithelium and it was suggested that it secretes a factor causing rafts aggregation to prepare uninfected cells for new infection [21]. Leishmania donovani also binds to lipid rafts of the macrophages using them as an entry gate; cholesterol depletion inhibits infection in vitro [22]. …”
Section: Pathogens Target Cellular Cholesterol Metabolismmentioning
confidence: 99%